“Yendo a lo seguro”. Análisis de los proyectos del ciclo 2022 del Presupuesto Participativo de San Lorenzo (Documentos y Aportes en Administración Pública y Gestion Estatal, 2025)
While a considerable amount of research has been conducted on Participatory Budgeting worldwide, only a few studies have focused on the specific projects discussed and selected within these processes. This article examines the projects submitted during the 2022 cycle of Participatory Budgeting in San Lorenzo, Argentina, with the hypothesis that both authorities and participants tend to prioritize small-scale projects, involving modest investments. Additionally, there is a preference for projects that resemble those executed in prior cycles and are aligned with the objectives of the local administration. More importantly, we argue that the influence over the type of projects resulting from the process does not necessarily lie solely with the authorities. Instead, participants themselves adjust their proposals and expectations to avoid potential feasibility or implementation issues.
Keywords: Participatory Budgeting; Project selection; Citizen Participation; Local Governments; Online Participation